2010
DOI: 10.1002/mrd.21203
|View full text |Cite
|
Sign up to set email alerts
|

High temperature causes masculinization of genetically female medaka by elevation of cortisol

Abstract: In poikilothermic vertebrates, sex determination is sometimes influenced by environmental factors such as temperature. However, little is known about the molecular mechanisms underlying environmental sex determination. The medaka (Oryzias latipes) is a teleost fish with an XX/XY sex determination system. Recently, it was reported that XX medaka can be sex-reversed into phenotypic males by high water temperature (HT; 32-34 degrees C) treatment during the sex differentiation period. Here we report that cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
162
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 34 publications
5
162
1
1
Order By: Relevance
“…Interestingly, this apparent absence of an action of cortisol on ovarian aromatase activity may not be the case for all fish species at all developmental stages. Two recent studies, one in the Japanese flounder (Paralichthys olivaceous) [37] and one in medaka (Oryzias latipes) [38] both provided evidence of cortisol promoting masculinization of genetically female fish, in part by acting to inhibit P450arom activity or the expression of P450arom genes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this apparent absence of an action of cortisol on ovarian aromatase activity may not be the case for all fish species at all developmental stages. Two recent studies, one in the Japanese flounder (Paralichthys olivaceous) [37] and one in medaka (Oryzias latipes) [38] both provided evidence of cortisol promoting masculinization of genetically female fish, in part by acting to inhibit P450arom activity or the expression of P450arom genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although Japanese medaka has a strong XY sex-determination system based on the sex-determining gene dmrt1bY located on chromosome Ola1 (O. latipes chromosome 1) (Matsuda et al 2002;Nanda et al 2002;Kondo et al 2006Kondo et al , 2009, environmental temperature can override the system and cause genotypic females to develop as phenotypic males (Sato et al 2005;Hattori et al 2007;Selim et al 2009;Hayashi et al 2010). We analyzed 21,909 RADtags (Table 1) from 30 female and 31 male medaka and conducted a G-test for genotypes that are significantly associated with male or female sex at 36,115 SNPs.…”
Section: Verifying the Rad-sex Method: Medakamentioning
confidence: 99%
“…Zebrafish does not, however, have a typical environmental sex-determination (ESD) mechanism like some sauropsids for which temperature is a cue (Charnier 1966;Lang and Andrews 1994;Merchant-Larios and Diaz-Hernandez 2013;Mork et al 2014). It is more probable that zebrafish is like medaka (Oryzias latipes) in having a genetic sex-determination mechanism that is sensitive to environmental conditions (Hattori et al 2007; Sato et al 2005;Selim et al 2009;Hayashi et al 2010).Zebrafish not only lacks classic ESD, but most stocks investigated do not have cytogenetically detectable chromosomal sex determination (Schreeb et al 1993;Pijnacker and Ferwerda 1995;Daga et al 1996;Gornung et al 1997;Amores and Postlethwait 1999;Gornung et al 2000;Sola and Gornung 2001;Traut and Winking 2001;Phillips et al 2006). In contrast, the only investigation of zebrafish taken directly from nature in India concluded that zebrafish females are the heterogametic sex (Sharma et al 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its potency as a regulator of intermediary metabolism in fish (Leatherland 2010, cortisol is involved in several aspects of normal gametogenesis and embryogenesis in fish. These include oocyte maturation and hydration (Milla et al 2006, hatching (Barry et al 1995, Sampath-Kumar et al 1995, sex differentiation (Hayashi et al 2010, embryo growth (Eriksen et al 2006, 2007, and modulation of the embryonic immune response . Thus, elevated cortisol levels in the oocytes, and therefore in early embryonic cells, have the potential to interfere profoundly with many aspects of normal embryogenesis (reviewed by Leatherland et al (2010Leatherland et al ( , 2012).…”
Section: Introductionmentioning
confidence: 99%